2011
DOI: 10.1007/s00726-011-1079-8
|View full text |Cite
|
Sign up to set email alerts
|

Bi-functional peptides with both trypsin-inhibitory and antimicrobial activities are frequent defensive molecules in Ranidae amphibian skins

Abstract: Amphibian skins act as the first line against noxious aggression by microorganisms, parasites, and predators. Anti-microorganism activity is an important task of amphibian skins. A large amount of gene-encoded antimicrobial peptides (AMPs) has been identified from amphibian skins. Only a few of small protease inhibitors have been found in amphibian skins. From skin secretions of 5 species (Odorrana livida, Hylarana nigrovittata, Limnonectes kuhlii, Odorrana grahami, and Amolops loloensis) of Ranidae frogs, 16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 32 publications
0
25
0
2
Order By: Relevance
“…The majority of BBI inhibitors are characterized by possession of a highly conserved canonical disulphide loop consisting of nine residues (CTP 1 SXPPXC, P 1 represents the reactive site residue) forming a short β ‐sheet . So far, several BBI‐like inhibitors of proteases have been identified in some species of ranid frogs such as Odorrana livida , Hylarana nigrovittata , Limnonectes kuhlii , Odorrana grahami and Amolops loloensis . Some of the BBI‐like inhibitors, like ORB from the skin secretion of Odorrana grahami and Ranacyclin‐T found in Rana temporaria , possessed bifunctions with both trypsin inhibitory and antimicrobial activities, while some of them, such as ORB2‐K (analogue of ORB) and pLR‐HL discovered in this study, displayed only trypsin inhibitory activity (Table ).…”
Section: Comparison Of Bowman–birk‐type Trypsin Inhibitors On the Primentioning
confidence: 99%
“…The majority of BBI inhibitors are characterized by possession of a highly conserved canonical disulphide loop consisting of nine residues (CTP 1 SXPPXC, P 1 represents the reactive site residue) forming a short β ‐sheet . So far, several BBI‐like inhibitors of proteases have been identified in some species of ranid frogs such as Odorrana livida , Hylarana nigrovittata , Limnonectes kuhlii , Odorrana grahami and Amolops loloensis . Some of the BBI‐like inhibitors, like ORB from the skin secretion of Odorrana grahami and Ranacyclin‐T found in Rana temporaria , possessed bifunctions with both trypsin inhibitory and antimicrobial activities, while some of them, such as ORB2‐K (analogue of ORB) and pLR‐HL discovered in this study, displayed only trypsin inhibitory activity (Table ).…”
Section: Comparison Of Bowman–birk‐type Trypsin Inhibitors On the Primentioning
confidence: 99%
“…We (as well as others) have recently demonstrated that certain inhibitors derived from amphibian skin secretions have a dual role possessing both antimicrobial and protease inhibitory activities . Since such compounds can be regarded as promising candidates for novel antibiotics, the further characterization of their properties is most interesting.…”
Section: Introductionmentioning
confidence: 96%
“…Since such compounds can be regarded as promising candidates for novel antibiotics, the further characterization of their properties is most interesting. It was demonstrated that synthetic disulfide‐bridged protease‐binding loops designed based on an inhibitor secreted by an oriental frog Odorrana graham (ORB) retain both the antimicrobial and trypsin inhibitory activities . Based on these findings, it became evident that the inhibitor binding loop plays an essential role in both functions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations